2012
DOI: 10.2340/00015555-1273
|View full text |Cite
|
Sign up to set email alerts
|

Living with Psoriasis: Prevalence of Shame, Anger, Worry, and Problems in Daily Activities and Social Life

Abstract: Psychosocial problems are frequent among patients with psoriasis. The aim of this study was to analyse the prevalence of some specific psychosocial issues. These were evaluated in 936 patients using the emotions and functioning scales of the Skindex-29 questionnaire. The problems most frequently experienced were: shame, anger, worry, difficulties in daily activities and social life. All problems were associated with the severity of psoriasis and with depression or anxiety. Shame, worry and annoyance were more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
150
0
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(172 citation statements)
references
References 35 publications
10
150
0
6
Order By: Relevance
“…The clinical type of palmoplantar 487 involvement had the greatest negative standardized 488 regression coefficient. This finding seems to be consistent 489 with earlier researches, which described that patients with 490 palmoplantar involvement have reported significantly 491 greater physical disability, discomfort, and work or leisure 492 impairment than those without palmoplantar involvement 493 [25,26]. In contrast, scalp psoriasis was the only variable 494 with positive unstandardized regression coefficient (b) 495 involved in the model.…”
supporting
confidence: 82%
“…The clinical type of palmoplantar 487 involvement had the greatest negative standardized 488 regression coefficient. This finding seems to be consistent 489 with earlier researches, which described that patients with 490 palmoplantar involvement have reported significantly 491 greater physical disability, discomfort, and work or leisure 492 impairment than those without palmoplantar involvement 493 [25,26]. In contrast, scalp psoriasis was the only variable 494 with positive unstandardized regression coefficient (b) 495 involved in the model.…”
supporting
confidence: 82%
“…In different studies, patients with psoriasis reported feelings of embarrassment and shame compared to healthy controls [74,75]. Shame is one of the most reported emotions, especially by women and by patients with a long disease duration [74].…”
Section: Stigmamentioning
confidence: 99%
“…Disfiguration, disability and marked loss of productivity are common challenges for people with psoriasis. There is also a significant cost to mental wellbeing, such as higher rates of depression ,leading to negative impact for individuals and society [13,14] .…”
Section: Int J Adv Res 5(1) 2793-2803mentioning
confidence: 99%